2019
DOI: 10.1108/jsocm-01-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

What if the company’s “charity of the year” is an organisation that deals with severe to moderate mental disability?

Abstract: Journal of Social MarketingWhat if the company's "Charity of the Year" is an organisation that deals with severe to moderate mental disability? A case study of fundraising problems and possibilities Structured AbstractPurpose: This paper explores the use of an ABC social marketing intervention to rescue a failing corporate "charity of the year" exercise that involved a mental disability charity. It describes the improvements experienced consequent to the introduction of volunteer "charity ambassadors" appointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…First, the experiments show the potential of LKM to elicit love. Developing a loving and compassionate attitude toward beneficiaries is a fundamental objective in social marketing programs, especially when working with stigmatized populations (Bennett and Vijaygopal, 2019). The reported evidence indicates that Buddhist-derived meditation such as LKM may be especially appropriate in these contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the experiments show the potential of LKM to elicit love. Developing a loving and compassionate attitude toward beneficiaries is a fundamental objective in social marketing programs, especially when working with stigmatized populations (Bennett and Vijaygopal, 2019). The reported evidence indicates that Buddhist-derived meditation such as LKM may be especially appropriate in these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This scholarship suggests that, because of its positive individual and social benefits, LKM has the potential to be added to the already proven effective and ethical programs for social good (French and Russell-Bennett, 2015). Specifically, meditation seems a suitable intervention within the ABC framework for social marketing interventions (Bennett and Vijaygopal, 2019), as it facilitates awareness of beneficiaries, nurtures a sense of connection with them and generates commitment to alleviate their suffering.…”
Section: Loving-kindness Meditation Nurtures Prosocial Dispositionsmentioning
confidence: 99%
“…The result is consistent with Tian (2019), as they asserted that belief could influence people's life events on life satisfaction. Prior studies argued that a proper social intervention could change consumers' attitudes and increase their patronage of a company that supports disabled employees (Bennett and Vijaygopal, 2019;Timke, 2019).…”
Section: Social Impact Beliefmentioning
confidence: 99%
“…Saleme et al (2020) suggested a social marketing program to improve empathy in children. Bennett and Vijaygopal (2019) found that within a company, the efforts of a few employees who persuaded other employees (e.g. not to feel Child sponsorships versus onetime donations distressed when interacting with mentally impaired individuals) resulted in an increase of 40% in charitable donations toward a charity concerned with mental disability.…”
Section: Theoretical Developmentmentioning
confidence: 99%